Interventions on School Physical Activity Incorporating the Ecological Model in LATAM: A Systematic Review - De Moraes-Ferrari, G (SAGE Publications Inc., 2025)
Meeting the recommendation of 60 minutes of daily physical activity for children and adolescents yields significant health benefits. In Latin-merican and the Caribbean, 39.1% of the population does not meet physical activity guidelines; specifically, 34.3% of males and 43.7% of females fall below the recommended levels. This study aims to identify school-based physical activity interventions aligned with the socioecological model that involve parents in Latina merican contexts. A systematic search was conducted across four databases—PubMed, Web of Science (WOS), Scopus, and ScienceDirect—for articles published between January 2014 and April 2024. A total of 198 studies were identified (78 from PubMed, 22 from WOS, 31 from Scopus, and 67 from ScienceDirect). After removing 20 duplicates, 167 articles were excluded based on title and abstract screening. One study was excluded. It focused on sedentary behavior, and another aspect was its consideration of dietary habits, resulting in a final inclusion of 9 studies. The included studies were published between 2014-2024, with intervention durations ranging from 10 weeks to 28 months and sample sizes from 50 to 3,592 participants. The studies were conducted in Ecuador, Colombia, Mexico, and Brazil. Interventions adopted both individual and environmental approaches, targeting outcomes such as physical activity, sedentary behavior, screen time, health education, nutrition, and alcohol and tobacco use. The reviewed intervention demonstrated positive effects on increasing physical activity and reducing sedentary behaviors. Family members, peers, friends, and teachers emerged as key sources of support for promoting health-enhancing behaviors, consistent with an ecological framework for health promotion. © 2025 Society for Public Health Education